Recategorization of tumor stage in patients with node‐negative oral tongue cancer: Impact of the eighth edition American Joint Committee staging system. Issue 9 (26th April 2019) - Dang, Rushil R.; Qureshi, Muhammad M.; Caldroney, Steven J.; Salama, Andrew R.; Truong, Minh Tam
Abstract: Background: To evaluate recategorization of pT1‐3N0 oral tongue cancer, from seventh to eighth editions of the American Joint Committee on Cancer (AJCC) staging classification, and impact on overall survival (OS). Methods: Using the National Cancer Database, 1277 patients were categorized using tumor size and depth of invasion with seventh and eighth AJCC staging systems and evaluated for OS. Results: Tumor‐category was unchanged in 82.9% and upstaged in 17.1% patients with eighth AJCC. The 3‐year OS was 85.3%, 76.6%, and 77.0% with seventh AJCC compared to 87.1%, 75.1%, and 81% with eighth AJCC, for patients with pT1N0, pT2N0, and pT3N0 disease, respectively. Improved discrimination of pT1N0 vs pT2N0 for OS on multivariate analysis was seen for eighth AJCC (hazard ratio [HR] = 1.43, 95% confidence interval [CI]: 1.03‐1.98, P  = .03) but not for patients with pT3N0, with seventh AJCC (HR = 1.02, 95% CI:0.53‐1.98, P  = .95), and eighth AJCC (HR = 0.86, 95% CI: 0.52‐1.42, P  = .55). Conclusion: Eighth edition AJCC staging leads to improved discrimination of OS between pT1N0 and pT2N0 but not for patients with pT3N0.